2016
DOI: 10.18632/oncotarget.12200
|View full text |Cite
|
Sign up to set email alerts
|

Supraclavicular and/or celiac lymph node metastases from thoracic esophageal squamous cell carcinoma did not compromise survival following neoadjuvant chemoradiotherapy and surgery

Abstract: This study is to evaluate the prognostic significance of supraclavicular and/or celiac lymph node (LN) metastases in locally advanced thoracic esophageal squamous cell carcinoma (ESCC) patients treated with neoadjuvant chemoradiotherapy (NACRT) and surgery. Among the total 199 patients, 75 (37.7%) had supraclavicular and/or celiac LN metastasis. Surgery was performed following NACRT in 168 patients (84.4%). After the median 18.7 (1.0-147.2) months’ follow-up, 2-year rates of progression-free survival (PFS) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 17 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Several previous studies have revealed that supraclavicular LN metastasis is not an independent prognostic factor for the survival of esophageal cancer patients 13 15 . However, the location of supraclavicular LNs is near the area of neck LNs in terms of anatomical distribution.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Several previous studies have revealed that supraclavicular LN metastasis is not an independent prognostic factor for the survival of esophageal cancer patients 13 15 . However, the location of supraclavicular LNs is near the area of neck LNs in terms of anatomical distribution.…”
Section: Resultsmentioning
confidence: 90%
“…In recent years, growing evidence has shown that supraclavicular LN metastasis is not associated with poor prognosis 13 , 14 , 20 , 21 . Cho et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies found that celiac LN metastasis does not compromise clinical outcomes [ 15 , 17 ]. A Korean study, reported by Cho et al ., showed metastasis to celiac LN was a significant factor neither for PFS nor OS in ESCC patients receiving neoadjuvant chemoradiotherapy and surgery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies found that celiac LN metastasis does not compromise clinical outcomes [ 15 , 17 ]. A Korean study, reported by Cho et al ., showed metastasis to celiac LN was a significant factor neither for PFS nor OS in ESCC patients receiving neoadjuvant chemoradiotherapy and surgery [ 15 ]. Another Japanese study, reported by Tachimori et al ., revealed the most predictive factor associated with lymph node metastasis for postoperative survival was not the area of involved nodes, but the number of involved nodes in ESCC patients receiving esophagectomy and three-field LN dissection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation